The Invisible Eye? Electronic Performance Monitoring and Employee Job Performance. Issue 3 (10th September 2013) - Bhave, Devasheesh P.
<x xml:space="preserve">Abstract</x> To enhance employee performance, many organizations are increasingly using electronic performance monitoring (EPM). The relationship between the frequency of EPM use and employee performance is examined in 2 field studies. In Study 1, which uses a unique longitudinal data set, results reveal that shorter time lags between 2 consecutive employee performance assessments are related to better task performance as indicated by call quality metrics. A second field study using matched supervisor–employee and EPM system data is conducted in 2 call centers to extend these results and to focus more directly on the supervisors' use of EPM and its relationship with additional performance criteria: counterproductive work behaviors (CWBs) and organizational citizenship behaviors (OCBs). Results indicate that more frequent supervisory use of EPM is associated with better task performance and OCB. However, supervisory use of EPM was not significantly related to CWB.